PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN BIOLOGI KELAS XI - Joko Kuswanto (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2019)
This study aims to develop android-based learning media on the subjects of biologi class XI. The research method used is research development with stages of designing, production, evaluation, and analyzing data by percentage. Based on different stages the trial was being done to experts: media experts (78,30) , the design (78), and the matter (80). So the percentage of overall value on the validation experts have eligibility criteria good. To scale individuals (80), small group (80,05) and field test (80,5). So the total value of the average percentage on of respondents with criteria good.